The Relationship of the Type of Intracerebral Hemorrhage to Early Disease Evolution and Long-Term Prognosis After r-tPA Thrombolysis. (16th April 2021) - Yang, Ting; Jing, Hongfei; Cao, Yungang; Lin, Xianda; Yan, Jueyue; Xiao, Meijuan; Huang, Xiaoyan; Cheng, Zicheng; Han, Zhao
To investigate the relationship of different subtypes of intracerebral hemorrhage (ICH) to early disease evolution and long-term prognosis in patients with acute cerebral infarction after intravenous recombinant tissue plasminogen activator(r-tPA). Seventy ischemic stroke patients treated with intravenous r-tPA who underwent computed tomography (CT) within 24 hours after thrombolysis were divided into 4 types (hemorrhagic infarction type 1 [HI-1], HI-2, parenchymal hemorrhage type 1 [PH-1], or PH-2 which according to the size of the hematoma and the presence or absence of space-occupying effect). Early evolution of the disease was observed by the change in the National Institutes of Health Stroke Scale (NIHSS) score within 24 hours after thrombolysis. The long-term prognosis was assessed by the modified Rankin Scale (mRS) score at the third month. There were 17 (24.3%) patients with ICH. Compared with patients in the non-ICH group, HI did not affect early neurological function or clinical outcome at the third month. PH-1 did not increase the risk of early neurological deterioration; however, PH-1 has a tendency to increase the risk of death at the third month (50% vs 11.3%, P = 0.090). PH-2 was significantly related to early neurological deterioration (66.7% vs 3.8%, P < 0.001) and mortality at the third month (50.0% vs 11.3%, P = 0.040). Patients with different subtypes of ICH after thrombolysis have different clinical outcomes. PH-2 is significantly associated with early neurological deterioration and increases mortality at the third month.